Convergence of Global Solutions to the Cauchy Problem for the Replicator Equation in Spatial Economics. (25th August 2016) - Tabata, Minoru; Eshima, Nobuoki
Abstract : We study the initial-value problem for the replicator equation of theN -region Core-Periphery model in spatial economics. The main result shows that if workers are sufficiently agglomerated in a region at the initial time, then the initial-value problem has a unique global solution that converges to the equilibrium solution expressed by full agglomeration in that region.